A NEW RECORD OF Euhampsonia roepkei Holloway, 1983 (LEPIDOPTERA: NOTODONTIDAE) FROM GUNUNG HALIMUN-SALAK NATIONAL PARK - Hari - Sutrisno (Masyarakat Zoologi Indonesia, 2009)
Notodontidae, a moderate family withinLepidoptera, consists of at least 3500species around the world. The speciesare mostly moderate to large in size withbiologically cryptic, but aestheticallypleasing wing patterns. The wings,especially the forewings, are usuallylonger and relatively narrow, as is theabdomen. The wing scaling is oftencoarse and the patterning never verycrisply defined.